DUAL PERSPECTIVES ON THE SUM OF TWO SQUARES: EXPLORING ONE OR TWO WAYS - Venkateswarlu, Velpula; Nagarani, Dharmarajula; Safeena, Md. (International Journal of Psychosocial Rehabilitation, 2019)
In mathematics, it has always been crucial to know how to express a natural number as the sum of two squares in one or both of the possible methods. Euler, Lagrange, Gauss, Dedekind, and many more eminent mathematicians have all provided positive answers to this topic. Using the idea of factorization of a number, we will present some good and simple methods in this paper for finding the numbers that may be expressed as the sum of two squares in one or two different ways